Redemption [videorecording (DVD)] - Knight, Steven, 1959-; Statham, Jason, 1967-; Buzek, Agata, 1976-; McClure, Vicky, 1983- (Distributed by Lions Gate Entertainment, 2013)
A damaged ex-special forces soldier trapped in the criminal underworld is transformed into an avenging angel when an unexpected opportunity allows him to assume another identity. Once believing he was beyond redemption, he now seeks out his own version of justice.